Dampak Aplikasi Islami Dalam Kegiatan Ibadah Sholat Bagi Generasi Z - Alan Tri Arbani Hidayat; Imamul Arifin; Aradhea Rangga (Tazkiya, 2022)
Generation Z is a generation that was born in an era of very rapid technological development. The rapidity of this technology makes this generation unable to stay away from what is called a Smartphone gadget or addiction, because the smartphone itself has a myriad of features and innovations that are very interesting. An example of innovation in religion is an Islamic application for prayer activities, Islamic applications provide various kinds of features that are easy to use. accessible, which is perfect for the tech-savvy Generation Z. We are hereby interested in conducting research with 0 Muslim respondents of generation Z through surveys and interviews, this study aims to find out how big the impact of Islamic applications in prayer activities for Generation Z is a case study of IT EEPIS students. Various opinions of respondents are presented and categorized so that from these opinions it is stated that Islamic applications have quite an impact on the spirit of generation Z to perform prayers.